Microdialysis to Optimize Cord Perfusion and Drug Delivery in Spinal Cord Injury. Issue 4 (19th August 2016) - Phang, Isaac; Zoumprouli, Argyro; Papadopoulos, Marios C.; Saadoun, Samira
Abstract : Objective: There is lack of monitoring from the injury site to guide management of patients with acute traumatic spinal cord injury. Here, we describe a bedside microdialysis monitoring technique for optimizing spinal cord perfusion and drug delivery at the injury site. Methods: Fourteen patients were recruited within 72 hours of severe spinal cord injury. We inserted intradurally at the injury site a pressure probe, to monitor continuously spinal cord perfusion pressure, and a microdialysis catheter, to monitor hourly glycerol, glutamate, glucose, lactate, and pyruvate. The pressure probe and microdialysis catheter were placed on the surface of the injured cord. Results: Microdialysis monitoring did not cause serious complications. Spinal cord perfusion pressure 90 to 100mm Hg and tissue glucose >4.5mM minimized metabolic derangement at the injury site. Increasing spinal cord perfusion pressure by ∼10mm Hg increased the entry of intravenously administered dexamethasone at the injury site 3‐fold. Interpretation: This study determined the optimum spinal cord perfusion pressure and optimum tissue glucose concentration at the injury site. We also identified spinal cord perfusion pressure as a key determinant of drug entry into the injured spinal cord. Our findings challenge current guidelines, which recommend maintaining mean arterial pressure at 85 to 90mm Hg for a week after spinal cord injury. We propose that future drug trials for spinal cord injury include pressure and microdialysis monitoring to optimize spinal cord perfusion and maximize drug delivery at the injury site. Ann Neurol 2016;80:522–531